2006
DOI: 10.1007/s00253-006-0405-7
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Trp59 and Trp60 in chitin-binding, hydrolytic, and antifungal activities of Streptomyces griseus chitinase C

Abstract: The chitin-binding domain of Streptomyces griseus chitinase C (ChBD(ChiC)) belongs to CBM family 5. Only two exposed aromatic residues, W59 and W60, were observed in ChBD(ChiC), in contrast to three such residues on CBD(Cel5) in the same CBM family. To study importance of these residues in binding activity and other functions of ChBD(ChiC), site-directed mutagenesis was carried out. Single (W59A and W60A) and double (W59A/W60A) mutations abolished the binding activity of ChiC to colloidal chitin and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Figure 3) and it is well known from e.g. the work by T. Watanabe and co-workers that these domains are important for binding to the substrate and hydrolytic efficiency Itoh et al, 2006). While the role of these domains in increasing substrate-affinity is well established (Boraston et al, 2004;, it is less clear whether these domains also may play a role is disturbing the crystalline packing of the substrate, thus making the substrate more accessible to enzymatic hydrolysis (see Eij sink et al, 2008 and references therein).…”
Section: Family 8 Chitosanasesmentioning
confidence: 90%
“…Figure 3) and it is well known from e.g. the work by T. Watanabe and co-workers that these domains are important for binding to the substrate and hydrolytic efficiency Itoh et al, 2006). While the role of these domains in increasing substrate-affinity is well established (Boraston et al, 2004;, it is less clear whether these domains also may play a role is disturbing the crystalline packing of the substrate, thus making the substrate more accessible to enzymatic hydrolysis (see Eij sink et al, 2008 and references therein).…”
Section: Family 8 Chitosanasesmentioning
confidence: 90%
“…The ligand molecule bound well on the surface-exposed tryptophans through two stacking interactions and two hydrogen bonds, and only Trp59 and Trp60 were involved in chitin binding. 27) In this study, it was found that ChBD of ChiJ probably interacted with crystalline cellulose (avicel), -1,3-glucan and -1,3-1,4-glucan, as well as chitin. Two tryptophan residues of ChBD of ChiJ, corresponding to Trp59 and Trp60 of ChiC, might interact also with crystalline cellulose, -1,3-glucan, and -1,3-1,4-glucan.…”
Section: Discussionmentioning
confidence: 97%
“…Stacking between sugar ligands and tryptophans in their cognate binding proteins/enzymes is known to be an important contribution to binding affinity in proteinglycan complexes [33,45,46]. Previous mutational studies of the conserved tryptophans in active chitinases have shown a reduction or complete loss of activity [45,47,48]. Owing to the conservation of the chitinase solvent-exposed/ligand stacking tryptophans in YKL-39, and their extensive interactions with the co-crystallized chitooligosaccharide ligand, it is likely that these residues are important for chitooligosaccharide binding.…”
Section: Ykl-39 Adopts a Chitinase-like Fold But Does Not Possess A Cmentioning
confidence: 99%